A study on E-Waste disposal practices among retailers in Taman Bendahara, Pengkalan Chepa - Muhammad Mirza Zulkifli; Nur Intan Shuhada Azli; Rosewann Ateera Mohamed Ridzuan; Teh Hwee Yee (2023)
The circular economy aims to achieve waste reduction, environmental protection, energy efficiency and economic growth. Using cost-effective waste management strategies, industrial waste can be remedied, reused and recycled. The transition from all sectors.